The Association of Acculturation with Overt and Covert Perceived Discrimination for Older Asian Americans. (3rd March 2020) - Chan, Keith
Abstract: Asian older adults are a fast-growing population in the United States. Because Asian older adults are a largely immigrant population, acculturation has an impact on their perceived discrimination, which is negatively associated with health and mental health. Discrimination can be overt, characterized by distrust and direct messages that are hostile and exclusionary, or covert, characterized by unfair treatment and messages that are negative and degrading. This study investigates the association of acculturation with perceived overt and covert discrimination, measured by the Everyday Discrimination Scale, with a sample of 348 foreign-born older Asian Americans from the National Latino and Asian American Study. Acculturation was measured by English-speaking ability, immigration-related variables, and ethnic identity. Results indicated that perceived covert discrimination was more prevalent than overt discrimination among older Asians. Among acculturation variables, only citizenship was associated with higher perceived covert and overt discrimination. Identifying with the same race was associated with higher covert discrimination. Findings suggest that higher acculturation is associated with greater exposure to discrimination for Asian older adults. Efforts to increase access and utilization of social and health-related services should consider the context of older Asians' experiences as a discriminated immigrant group in the United States.